Diagnostic Accuracy of Magnetic Resonance Imaging in Detection of Paediatric Cerebellar Astrocytoma - SAIMA AMEER, ALEENA KHAN, NIGHAT HAROON, WAJEEHA AKBAR, (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the diagnostic accuracy of Magnetic Resonance imaging in the detection of paediatric cerebellar astrocytoma taking histopathology as gold standard. Study Design: Cross-sectional survey Place and Duration of Study: Department of Diagnostic Radiology, Lahore General Hospital, Lahore from 23-11-2014 to 22-05-2015. Methodology: In this cross sectional study all 210 patients presenting with clinical suspicion of posterior fossa tumor meeting the inclusion criteria were taken. All the patients were recorded for their demographic features i.e. age, gender and address. Magnetic resonance imaging on a 1.5-T Philips whole body MR system using standard imaging coil were then be carried out. T2-weighted and both unenhanced and contrast-enhanced T1-weighted images in the axial, sagittal and coronal projections were obtained. Magnetic resonance imaging diagnosis i.e. presence or absence of cerebellar astrocytoma were recorded by same observer. The cases (with posterior fossa tumor) were operated and histopathological results were recorded. The results of magnetic resonance imaging and histopathology were compared taking histopathology as gold standard. Results: The mean age of patients in this study was 9.26±1.06 with minimum and maximum reported ages of 6.0 years and 13.0 year respectively. There were118 (56.2%) male and 92 (43.8%) female patients in this study. The overall diagnostic accuracy of MRI was 90% keeping histopathology as gold standard. The sensitivity and specificity of MRI was 90.91% and 86.67% respectively. The positive predictive value and negative predictive values of MRI were found as 96.15% and 72.22% respectively. Conclusion: The sensitivity and specificity of MRI was 90.91% and 86.67% respectively. So, it is suggested MRI should be done in patients with suspicion of posterior fossa tumor as it is reliable, non-invasive, easily available and ionizing radiation free imaging modality which allows early detection, precise localization and characterization of posterior fossa tumours because of its multiplanar and multi-parameter capabilities.